Development of a Simple Tray Aerator Physical Model to Improve Groundwater Quality in Bonti Village, Sanggau Regency - Adlillah, Miftakhul; Umar, Umar; Yulianto, Eko (Jurnal Teknik Sipil, 2025)
The community of Bonti Village relies on groundwater as the primary source of clean water since the local Regional Drinking Water Company (PDAM) ceased operations. However, the quality of the groundwater often raises health concerns, particularly in cases of diarrhea during the dry season. This study aims to design and evaluate the performance of a simple tray aerator as an alternative technology for groundwater treatment to meet the quality standards set by the Regulation of the Minister of Health of the Republic of Indonesia No. 2 of 2023 on Mandatory Drinking Water Quality Parameters. The design consists of four tray levels and one storage container, with a spacing of 0,4 m between trays and a container height of 0,3 m. Each tray measures 0,42 m in length and 0,30 m in width, equipped with 88 holes of 0,005 m diameter and a spacing of 0,03 m between holes. The total hole area was recorded at 0,001727 m ², with a surface loading rate of 6,6665 m ²/m ³/s and a detention time of 1,16 seconds. The filtration media used include charcoal (2 cm), shell sand (2 cm), gravel (1,5 cm), and coconut fiber (1,5 cm). The groundwater quality tests from three bore wells indicated a significant reduction in metal concentrations and improvements in both physical and chemical parameters, with all parameters meeting the required quality standards. Therefore, the simple tray aerator is proven to be effective as an appropriate technology solution for the provision of clean water in rural areas.